SIMULATION STUDY ON THE LOST SALES INVENTORY SYSTEMS WITH ATTACHED SERVICE QUEUE - Park, Jinsoo; Baek, Jung Woo; Kim, Yun Bae (International Journal of Industrial Engineering: Theory, Applications and Practice, 2017)
In this paper, we consider a queueing system with an attached inventory. Customers arrive in the system according to a general arrival process, and a single server serves the customers in order. The service times are assumed to be independent and identically distributed (i.i.d.) random variables. At the service completion epoch, a customer departs the system with exactly one item from the attached inventory storage. If the inventory level drops to zero, the service is paused, and the remaining customers in the queue should wait in the system until the inventory is replenished. Potential sales from customers who arrive during this stockout period are lost. The service process is resumed as soon as the stock is replenished. The inventory is usually managed by one of the popular inventory control policies such as the (r, Q) or (s, S) policy. We design the simulation experiments under various inter-arrival time, service time, and lead time distributions with several parameter settings to evaluate the system performances. The operational characteristics of the proposed inventory systems are investigated, and the cost models are presented.